Phylogenetic position inferred on SSU rDNA sequence gene and description of a new parasitic cnidarian (Endocnidozoa: Myxobolidae) infecting Markiana nigripinnis (Teleostei: Stevardiinae) from a small marginal lake floodplain, Brazil - Mota, Maria E.B.P.; Mathews, Patrik D. [UNESP]; Milanin, Tiago; Mertins, Omar; Paiva, Fernando; Oliveira, Carina E.; Tavares, Luiz E.R. (My University, 2024)
Herein, a detailed molecular phylogeny analysis was developed to determine the phylogenetic position of a new freshwater histozoic myxosporean cnidarian, Henneguya markiana sp. nov. from the world’s largest tropical wetland area, Pantanal, Brazil. The new species is described using an integrative taxonomy approach including morphology, biological traits and molecular data. Phylogenetic analysis inferred by Maximum Likehood method showed the new Henneguya species in a well-supported clade of myxosporean gill parasites of South American characids fishes. In this same clade, the new Henneguya described appeared in a sub-clade clustering with H. lacustris and H. chydadea. Nevertheless, the sequences of the new species and H. lacustris and H. chydadea have a large genetic divergence of 10.4% (148 nucleotides-nt) and 10.5% (147 nt) respectively. To the best of our knowledge, this is the first report of a cnidarian myxosporean species parasitizing a fish from Stevardiinae from South America. In the light of the differences observed from the integrative taxonomy, we are confident that this isolate is a new species of Henneguya, increasing the knowledge of diversity of this enigmatic group of cnidarians.
Keywords: Biodiversity; Gill parasites; Myxosporean; Phylogeny; Tetra fish